Performance of zinc oxide particles as liquid ethanol sensor. (2019) - Hamid, H.A.; Lockman, Z.; Hattori, T.; Razak, K.A.
Abstract: In this work an electrode for detection of ethanol has been developed using zinc oxide (ZnO) particles grown by annealing process with zinc oxide seeds. Zinc oxide particles were grown on an indium tin oxide (ITO) substrate and accumulated in globular shapes. The morphology and crystallinity of the ZnO/ITO were determined by field emission scanning electron microscopy (FESEM) and X-ray diffractometer (XRD). The diameter of particles was ∼50 to 58 nm. The ZnO/ITO electrode was used to detect ethanol in liquid in the range of 7-25 mM by using three electrodes cyclic voltammetry (CV) system in 1M potassium hydroxide (KOH) electrolyte solution. The ZnO/ITO electrode shows high sensitivity of 8.14 µAmM -1 .cm -2, with detection limit of 2.4 mM and linear correlation coefficient of 0.9682. Therefore, ZnO/ITO electrode has an excellent potential as the ethanol sensor in liquid.